2004
DOI: 10.1111/j.1467-839x.2004.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Super‐ordinary bias in Japanese self‐predictions of future life events

Abstract: Japanese are said to value being ordinary and emphasize similarity with others. We theorized that Japanese tend to perceive themselves as being ordinary, so much so that their self-predictions about future life events are biased (superordinary bias). Specifically, it was expected that Japanese overestimate the likelihood of experiencing common events (such as getting married or catching the flu) and underestimate the likelihood of experiencing rare events (such as winning a lottery or being murdered). We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…In cross-cultural studies using the indirect method to measure comparative optimism (which happen to be very few), Westerners tend to be unrealistically optimistic, whereas Easterners tend to be unrealistically pessimistic or neutral (neither optimistic nor pessimistic) (see review in . Such results might reflect differences in cross-cultural prototypes of the average person (i.e., more negative prototypes in Western cultures) or they may be a manifestation of an Eastern/interdependent motivation to be self-critical and not to differentiate the self from others (see work on the superordinary bias in Ohashi & Yamaguchi, 2004) versus a Western/independent motivation toward self-enhancement and superior differentiation from others Markus & Kitayama, 1991). Such motivational patterns in comparative judgments may only be detected when using indirect (as opposed to direct) methods because robust cognitive processing biases, such as differential weighting, are not influential for the indirect method and thus do not dominate the result patterns for that method.…”
Section: Cognitive and Measurement Factors In Comparative Biasesmentioning
confidence: 99%
“…In cross-cultural studies using the indirect method to measure comparative optimism (which happen to be very few), Westerners tend to be unrealistically optimistic, whereas Easterners tend to be unrealistically pessimistic or neutral (neither optimistic nor pessimistic) (see review in . Such results might reflect differences in cross-cultural prototypes of the average person (i.e., more negative prototypes in Western cultures) or they may be a manifestation of an Eastern/interdependent motivation to be self-critical and not to differentiate the self from others (see work on the superordinary bias in Ohashi & Yamaguchi, 2004) versus a Western/independent motivation toward self-enhancement and superior differentiation from others Markus & Kitayama, 1991). Such motivational patterns in comparative judgments may only be detected when using indirect (as opposed to direct) methods because robust cognitive processing biases, such as differential weighting, are not influential for the indirect method and thus do not dominate the result patterns for that method.…”
Section: Cognitive and Measurement Factors In Comparative Biasesmentioning
confidence: 99%
“…Unlike independent North Americans who emphasize the value of uniqueness, interdependent East Asians are known to value modesty and harmony (Markus and Kitayama, 1991). In addition, it is suggested that East Asians may have a strong motivation to see oneself as normal and ordinary and hold a belief that being ordinary is safe and also beneficial (e.g., Ohashi and Yamaguchi, 2004). Overestimating the consensus on one's own position is one way to acquire the sense of "ordinariness"; however, underestimating the consensus of alternative position can be another way to achieve it, and this pattern seems to have contributed to a greater FCE in Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a cross-cultural comparison, Kitayama et al (1990, unpublished, as cited in Markus and Kitayama, 1991) found that this pattern was slightly reversed for Indians: they judged that the self is more similar to the other than the other is to the self. Ohashi and Yamaguchi (2004) also noted that Japanese seemed to perceive being ordinary or average as safe and satisfying; further, they even make normative self-predictions about their future life events. More specifically, Japanese tend to predict that in comparison with the average person, they are more likely to experience common events rather than rare events.…”
Section: Culture and Perception Of Consensusmentioning
confidence: 98%
“…日本人には自分を「ふつう」よりも「ふつう」であると知覚する傾向がある (Ohashi & Yamaguchi, 2004) Cole, 1996;Shweder, 1990)と固有文化心 理学 (indigenous psychology; e.g., Kim & Berry, 1993) (Bruner, 1990) Lebra, 1976;Markus & Kitayama, 1991) 。また,1980 年代 以降脚光を浴びてきた個人主義・集団主義の程度という 文化の説明軸 (Triandis, 1989;Kim, Triandis, Kagitcibasi, Choi, & Yoon, 1994) Kim et al, 1994;Triandis, 1989…”
unclassified
“…Japanese have a biased tendency to view themselves as being more ordinary than ordinary people (Ohashi & Yamaguchi, 2004). The existence of such bias, which overemphasizes one's ordinariness, suggests that being ordinary person may be desirable in Japanese culture.…”
mentioning
confidence: 99%